Interaksi Sosial Anak-anak di Sanggar Bhineka Pencegahan, Pemberantasan, Penyalahgunaan dan Peredaraan Gelap Narkoba (P4GN) Kab. Sukoharjo - Riska Nabillaahadyah; Endah Fajri Arianti (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Sanggar Bhineka P4GN Sukoharjo, a community that focuses on developing children's knowledge, character and social skills. The volunteers at Sanggar Bhineka are students/internship students from various universities in Solo Raya and have the same goal. Data collection was carried out using a qualitative approach, namely participant observation and more in-depth interviews with children. The results of the research show that the activities carried out in the studio, such as fun games, learning and creative activities, still do not contribute significantly to improving the communication skills of some children. These findings emphasize the importance of an educational environment that supports social interaction for the development of children's character, so that children can express themselves and improve their communication skills.